Developing a Teaching Methodology of Translation Course : A Cooperative Learning Model for English Department Students - Fransisca Novitasari; Priyatno Ardi (Indonesian Journal of English Language Studies (IJELS), 2016)
The article, firstly, analyzes some basic concepts of translation and cooperative learning model. Further, a design of translation course’s syllabus for an undergraduate level is described. In addition, an example of lesson plan and an example of students’ analysis are elicited. The teaching methodology consists of a step-by-step procedure which adopts the cooperative learning model. In this cooperative learning model, the educator is understood as a facilitator, whose role is providing the materials, checking the students’ understanding, giving feedback, and evaluating the failures and the weaknesses of the knowledge-transfer- process. Therefore, the transfer process of translation theory and practice is mainly accomplished by the students, collectively and individually. Overall, the implementation of cooperative learning model in the design and procedure of translation course is viewed as an effective way to improve the ability of students in translating English text into Indonesian and in translating Indonesian text into English.